2014
DOI: 10.1210/jc.2013-3612
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease, Liver Fibrosis, and Cardiometabolic Risk Factors in Adolescence: A Cross-Sectional Study of 1874 General Population Adolescents

Abstract: Context:The impact of adolescent nonalcoholic fatty liver disease (NAFLD) on health, independent of fat mass, is unclear.Objective:The objective of the study was to determine the independent (of total body fat) association of ultrasound scan (USS)-determined NAFLD with liver fibrosis, insulin resistance, and dyslipidemia among healthy adolescents.Design:This was a cross-sectional analysis in participants from a UK birth cohort.Participants:One thousand eight hundred seventy-four (1059 female) individuals of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 26 publications
(38 reference statements)
1
82
0
2
Order By: Relevance
“…We were unable to examine change in other measures of adiposity (such as DXA determined total (or trunkcal) fat mass or waist circumference) with liver outcomes in this study as these measurements were not undertaken in infancy and early childhood in ALSPAC. However, our earlier publication shows the relationships of BMI, DXA determined total and trunkcal fat mass with hepatic outcomes are similar [42]. In this study we used AUDIT to assess alcohol consumption in all participants.…”
Section: Discussionmentioning
confidence: 86%
“…We were unable to examine change in other measures of adiposity (such as DXA determined total (or trunkcal) fat mass or waist circumference) with liver outcomes in this study as these measurements were not undertaken in infancy and early childhood in ALSPAC. However, our earlier publication shows the relationships of BMI, DXA determined total and trunkcal fat mass with hepatic outcomes are similar [42]. In this study we used AUDIT to assess alcohol consumption in all participants.…”
Section: Discussionmentioning
confidence: 86%
“…17 More recently, it was reported that the prevalence of NAFLD in healthy European adolescents was estimated to be 2.5% based upon evaluation with ultrasound. 18 Multicenter population studies in Europe estimated a higher prevalence of NAFLD based upon ultrasound evaluation in adults than that observed in children (Spain: 33.4% men and 20.3% women; Italy: 33% in men and 20% in women). 19,20 It is important to acknowledge that there are limitations of both ALT and ultrasound which can both underdiagnose NAFLD because of inadequate sensitivity for detecting NAFLD and over diagnose NAFLD because abnormal findings are not specific for NAFLD.…”
Section: Epidemiologymentioning
confidence: 97%
“…Nonalcoholic fatty liver disease (NAFLD) has been rapidly emerging among children and adolescents and is now the most common cause of chronic liver disease in the developed world [2,15,26]. Adolescents with NAFLD also tend to be more insulin resistant and dyslipidemic, but the extent to which these associations are independent of total body fatness is not clearly understood [1,5,27].…”
Section: Introductionmentioning
confidence: 99%